Tacit knowledge development in a new product development teaching simulation - Goffin, Keith; Baxter, David; Szwejczewski, Marek; Cousens, Alan; van der Hoven, Christopher (Cranfield University, 2010)
This paper describes our evaluation of whether participants perceive that they have developed new tacit knowledge during a New Product Development simulation. We assess this by asking the participants their key lessons learnt during the exercise, followed by the perceived level of ‘tacitness' of those lessons. We find that participants do not perceive these lessons learnt to be tacit. A second questionnaire finds that participants believe that the practical experience gained during the simulation would improve the performance of a subsequent project, but that extended classroom teaching would not. This discrepancy is thought to highlight the lack of a suitable measure for tacitness. Future studies should focus on experience variables rather than codification variables when assessing the development of tacit knowledge in teaching activitie